Current status and distribution of major RNA viruses infecting onion and garlic crops in Punjab, Pakistan - Hamza, Muhammad Zubair; Ashfaq, Muhammad; Riaz, Hasan; Saeed, Shafqat (Emirates Journal of Food and Agriculture, 2023)
Onion (Allium cepa L.) and garlic (Allium sativum L.) are significant bulbous vegetables well known for their kitchen and medicinal values across the globe including Pakistan. Allium crops are highly vulnerable to many notorious RNA viruses fit in different genera viz., Allexivirus, Potyvirus, Tospovirus and Carlavirus. These viruses are known to inflict colossal and havoc yield losses up to 50% in allium crops wherever they grown. The occurrence of allium viruses in Pakistan has already been reported, but in single crop and only a few studies describe their incidence and distribution. The study examined the current scenario and distribution of major RNA viruses infecting Allium crops in Punjab, Pakistan. Field surveys were carried out in 14 districts of Punjab province as well as capital territory Islamabad of Pakistan, for two consecutive growing seasons (2019 and 2020). The 3000 leaf samples collected, 1675 samples (Onion 791, Garlic 884) were found positive for RNA viruses by using specie specific DAS-ELISA and further confirmed through reverse transcriptase polymerase chain reaction (RT-PCR). The results revealed the presence of RNA viruses with overall disease incidence of 52.7% and the highest disease incidence was observed as Onion yellow dwarf virus (OYDV) 58% following Irish yellow spot virus (IYSV) 41.8% respectively in onion crop during 2019-2020. Similarly, in garlic crop overall disease incidence of RNA viruses was noticed as 58.9% and the highest disease incidence of OYDV was observed as 45%, following IYSV 32.4% and GarV-C 22.5% respectively during 2019-2020. Comparatively, disease incidence and geographical distribution of viruses was variable in surveyed regions of both crops during surveyed period, whereas OYDV and IYSV were most prevalent viruses infecting onion and garlic crops and GarV-C found only in garlic. The current study also concluded the importance to disseminate the information/awareness among the farmers regarding viral diseases and their management by using different strategies including use of resistant genotypes. Keywords: Allium crops; RNA viruses; ELISA; RT-PCR; Disease incidence; Virus distribution